2019
DOI: 10.1136/bmjopen-2019-032759
|View full text |Cite
|
Sign up to set email alerts
|

Components of the full blood count as risk factors for colorectal cancer detection: a systematic review protocol

Abstract: IntroductionColorectal cancer is the fourth most common type of cancer and the second most common cause of cancer-related deaths in the UK. The full blood count (FBC) is a blood test that may play a role in early detection of the disease. Previous studies have aimed to identify how levels of individual components, such as haemoglobin, can be used to assist the diagnosis. We aim to systematically review studies to identify whether components of the FBC are risk factors for diagnosis of colorectal cancer, critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Ethical approval was not required as there were no direct patient investigations in this study and only published articles were systematically reviewed. The review protocol was registered with the International Prospective Register of Systematic Reviews database on 13th May 2019 (PROSPERO: CRD42019134400) and has previously been published [ 7 ]. We provide a summary of the methods used here and details of new methods employed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical approval was not required as there were no direct patient investigations in this study and only published articles were systematically reviewed. The review protocol was registered with the International Prospective Register of Systematic Reviews database on 13th May 2019 (PROSPERO: CRD42019134400) and has previously been published [ 7 ]. We provide a summary of the methods used here and details of new methods employed.…”
Section: Methodsmentioning
confidence: 99%
“…Data was extracted using two self-designed extraction forms in Microsoft Excel: the risk factors form (for Aim 1) and the prediction models form (for Aim 2). Data items from both forms are listed in the protocol [7]. If a study developed a prediction model, where some FBC components were analysed but not included in the model, these FBC components were collected in the risk factors form and the model details collected in the prediction model form.…”
Section: Data Extractionmentioning
confidence: 99%
“…Our recent systematic review identified 53 studies that assessed the FBC blood test for colorectal cancer diagnosis 4,5 . Our review indicated that diagnosed patients have a significantly lower red blood cell count, haemoglobin, and mean corpuscular volume and higher red blood cell distribution width, white blood cell count, and platelets within six months of diagnosis compared to patients not diagnosed.…”
Section: Introductionmentioning
confidence: 99%